EMPOWERING CULTURAL IDENTITY THROUGH NON-FORMAL EDUCATION: A QUALITATIVE STUDY OF ZAPIN PECAH DUA BELAS DANCE - Suryani, Nike; Jazuli, M; Cahyono, Agus; Ibnan Syarif, M (JURNAL EDUSCIENCE, 2025)
Purpose – This study aims to investigate the role of non-formal education in strengthening cultural heritage through learning the Zapin Pecah Dua Belas dance in the local community of Riau. As an essential part of the Malay cultural tradition, this dance faces the threat of fading due to modernization and a lack of structured preservation efforts.Methodology – This research used a qualitative case study design method. Data was collected through participant observation and in-depth interviews with participants from community leaders. This research focused on the dance studio community's active involvement in the Zapin dance.Findings – The study results show that non-formal education is important in preserving local cultural heritage. This fishing process provides special skills to the dancers in moving and gathering a deep understanding of the meaning of values and cultural identity contained in the Zapin tradition. This learning process provides opportunities and encourages community involvement that strengthens the sustainability of culture among young generations in the future.Contribution – The novelty of this study lies in its emphasis on a holistic, non-formal educational approach that integrates both the technical and cultural dimensions of traditional dance. It contributes to developing educational strategies that reinforce cultural identity and heritage through community-based learning initiatives.